Antibacterial Capabilities of Metallic Nanoparticles and Influencing Factors - Abayeneh Girma; Gedefaw Mebratie; Bawoke Mekuye; Birhanu Abera; Tigabu Bekele; Getachew Alamnie (Nano Select)
ABSTRACT The increase of antibiotic resistance in bacteria has become a major concern for successful diagnosis and treatment of infectious diseases. Over the past few decades, significant progress has been achieved on the development of nanotechnology‐based medicines for combating multidrug resistance in microorganisms. Among these, metallic nanoparticles (MNPs) hold great promise in addressing this challenge due to their broad‐spectrum and robust antimicrobial properties. This review illustrates the antibacterial activities of MNPs and further elucidates how different factors including synthesis method, size, shape, surface charge, pH, dose, type of capping or stabilizing agents of MNPs, and Gram‐type of the bacteria, impact their antibacterial activities, which are expected to promote the future development of more potent MNP‐based antibacterial agents.